Correlation between crystal warpage and swelling of 4H-SiC through implantation and annealing. (27th August 2020) - Ishiji, Kotaro; Sato, Kiichi; Fujii, Takashi; Araki, Tsutomu; Mouri, Shinichiro; Sugie, Ryuichi
Abstract: Crystal warpage and swelling of implanted 4H-SiC with both un-implanted and implanted regions on the surface were investigated using a white-light interferometer. In the SiC samples with an implantation temperature of approximately 30 °C, the warpage was small and the step at the un-implanted/implanted interface for swelling was large. In contrast, the SiC samples with implantation temperatures of over 300 °C had a large warpage and a small interface step. In the x-ray topographs, no diffraction at the interface was observed in the SiC implanted at a low temperature; however, the SiC implanted at a high temperature exhibited diffraction at the interface. Diffraction at the interface is evidence of lattice bonding between the un-implanted and implanted regions. The interfacial lattice bonding can consistently explain the correlation between the crystal warpage and the swelling of the implanted SiC. After the annealing, crystal recovery developed and the warpage and swelling returned to their initial state in all samples.